(untitled) (Journal of Hama University, 2026)
The experiment was carried out at the Saalo Research Station of the Deir ez-Zor Research Center to study the effect of fertilization with iron and zinc and their interaction on durum wheat (Sham 7) during the 2023-2034 seasons. Zinc sulfate was used as a source of zinc at three concentrations (4, 6, 8) kg/ Ha. Ferrous sulphate was also used as a source of iron at three concentrations (8, 12, 16) kg/ha, in addition to the interaction between iron and zinc The application process was carried out before planting during the land preparation process, and nitrogen and phosphorus fertilizers were added according to the recommendation of the Ministry of Agriculture The results showed the emergence of significant differences between the studied treatments, and the T9 treatment was superior in the plant height index, while no clear significant differences appeared between the treatments in the spike length index. The T15,T9 treatments also excelled in the spike weight, 1000-seed weight, and productivity indicators.